Spatiotemporal role of SETD2-H3K36me3 in murine pancreatic organogenesis - Ping Lu; Junyi Xu; Xuqing Shen; Jiajun Sun; Mingzhu Liu; Ningning Niu; Qidi Wang; Jing Xue (Cell Reports, 2024)
Summary: Pancreas development is tightly controlled by multilayer mechanisms. Despite years of effort, large gaps remain in understanding how histone modifications coordinate pancreas development. SETD2, a predominant histone methyltransferase of H3K36me3, plays a key role in embryonic stem cell differentiation, whose role in organogenesis remains elusive. Here, by combination of cleavage under targets and tagmentation (CUT&Tag), assay for transposase-accessible chromatin using sequencing (ATAC-seq), and bulk RNA sequencing, we show a dramatic increase in the H3K36me3 level from the secondary transition phase and decipher the related transcriptional alteration. Using single-cell RNA sequencing, we define that pancreatic deletion of Setd2 results in abnormalities in both exocrine and endocrine lineages: hyperproliferative tip progenitor cells lead to abnormal differentiation; Ngn3+ endocrine progenitors decline due to the downregulation of Nkx2.2, leading to insufficient endocrine development. Thus, these data identify SETD2 as a crucial player in embryonic pancreas development, providing a clue to understanding the dysregulation of histone modifications in pancreatic disorders.